COMBINING ABILITY OF MAIZE STRAINS IN LOW NITROGEN NUTRITION - Aulianta, Ladikta Hubah; Santoso, Juli; Makhziah; Mejaya, I Made Jana (jfpublisher, 2022)
The nitrogen reduction in soil is a problem in maize cultivation that can cause production decrease. The efforts to prevent this problem is to assemble superior maize that is low nitrogren resistance and high production by crossing different corn former plants. This research was to analyze the combining power of five strains (G1, G2, G3, G4 and G5) under normal and low nitrogen conditions used a half diallel cross design by Griffing I method formula to analyze 10 genotypes. The research design used a divided plot design (RPT) with 3 replications, the research location was in the experimental garden of Balai Pengkajian dan Teknologi Pertanian in Kebondalem village, Mojosari district, Mojokerto district and the application of nitrogen fertilizer. The value of the general combining ability (DGU) of the G3 elders significantly affected the weight parameters of the cobs under low nitrogen conditions. The results of the special combining ability (DGK) on the G7 and G8 crosses had high DGK values on harvest character and weight of 100 seeds under normal and low nitrogen conditions. The genotype G6 has a high DGK value for cob weight characters.